Employee Productivity Optimization through Training, Discipline, and Work Motivation - Fauzan, Alvin (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This research aims to determine the influence of job training, work discipline, and work motivation, either partially or simultaneously, on employee productivity at PT. Bank DKI, Permata Hijau Cluster. This study employs a quantitative method with a descriptive analysis approach through a survey. The population of this research consists of 212 employees at PT. Bank DKI, Permata Hijau Cluster, while the sample size is determined using Slovin's calculation, resulting in 139 respondents. The analysis techniques include validity test, reliability test, classical assumption test, linear regression analysis, coefficient test, determination test, and hypothesis test. The research findings indicate that job training, work discipline, and work motivation have a positive and significant impact on work productivity, as evidenced by the F-value of 58.063 > F-table 2.67 and an Adjusted R Squared value of 55.4%. This implies that approximately 55.4% of the variation in work productivity can be explained by the combined effects of job training, work discipline, and work motivation.